Downscaling, projection, and analysis of expected future climate change in a watershed of Omo-Gibe basin of Ethiopia - Toma, Meseret Bekele; Ulsido, Mihret Dananto; Bitew, Alemayehu Muluneh; Meja, Merihun Fikiru (Frontiers in Water, 2024)
The purpose of this study was to investigate the rainfall and temperature changes for the projected periods of (2021–2050) and (2051–2080) under two Representative Concentration Pathways (RCP4.5 and RCP8.5) at selected stations in the Ajora-Woybo watershed of Omo-Gibe basin, Ethiopia. CORDEX-Africa with the Coupled Models Intercomparison Project Phase 5 (CMIP5) has been used to downscale the future climate change (2021–2050 and 2051–2080). The RCPs scenarios RCP4.5 and RCP8.5 were considered for this study. The climate model data for hydrological modeling (CMhyd) were used for extraction of CORDEX-NetCDF and the rainfall and temperature bias correction. The monthly observational and reanalysis rainfall and temperature data were validated with ground observations using statistical measures such as the mean relative error (MRE), the correlation coefficient (CORR), and the Nash-Sutcliffe efficiency coefficient (NSE). The simulation performance evaluation revealed that all of the chosen global circulation models (GCMs) have good simulation capacity over the Ajora-Woybo watershed. The predicted mean annual RF shows a non-significant decline in the ensemble GCMs’ for the two time periods 2021–2050 and 2051–2080. In comparison to the RCP 8.5 emissions scenario, rainfall is expected to decline less under the RCP 4.5 climate change scenario. For ensemble GCMs, it is anticipated that mean annual Tmax and Tmin would both rise in comparison to the baseline at all stations. The Tmax and Tmin trends at the end of the 2040s and 2070s changed more in the highest emission scenario, RCP8.5, than in the RCP4.5 scenario. In order to reduce ongoing effects of climate change and create long-term water resource management plans for the Ajora-Woybo watershed, it will be helpful to consider projected changes in temperature and rainfall.